Implementasi Alat Peraga dalam Mendukung Pembelajaran Soal Higher Order Thinking Skills Pada Materi Dimensi Tiga di SMA Negeri 8 Kota Bengkulu - Sari, Ratna Puspita; Melsijoza, Diva; Haliza, Dwi Nur; Apriyany, Adinda Dewi; Mareccha, Ulva Annatri; Augustien, Bintang; Miqdat, Pebrian; Utari, Tria (Universitas Pahlawan Tuanku Tambusai, 2025)
Students' difficulties in understanding HOTS questions on three-dimensional material are mainly caused by their weak ability to visualize three-dimensional space and apply abstract concepts such as the Pythagorean Theorem in space. This finding is intended to improve the capabilities of grade 12 students of SMAN 8 Kota Bengkulu in solving HOTS questions through the implementation of teaching aids. The research method used qualitative with descriptive methods. Teaching aids in the form of a spatial framework and ropes were used to make it easier for students to visualize three-dimensional concepts. The results of the study provide evidence that the use of teaching aids helps students understand the tangency between points, lines, and planes in three-dimensional space, as well as improve their skills in using the Pythagorean formula. The conclusion of the study is that teaching aids significantly improve students' understanding of the concept of three dimensions and their ability to solve HOTS questions.